Eco-Friendly Textile Dyeing and Finishing - Günay, Melih (IntechOpen, 2013)
Human genetics is the medical field with the most rapid progress. This book aims to provide an overview on some of the latest developments in several genetic diseases. It contains 14 chapters focused on various genetic disorders addressing epidemiology, etiology, molecular basis and novel treatment options for these diseases. The chapters were written by 41 collaborators, from 8 different countries in Europe, Asia, and America, with great expertise in their field. Chapters are heterogeneous, offering a welcomed personalized view on each particular subject. The book does not offer a systematic overview of human genetic disorders. However, they are a valuable resource for medical practitioners, researchers, biologists and students in various medical sciences.